Cache Content Placement Optimization in Non-Orthogonal Multiple Access Networks - Li, Yiqing; Jiang, Miao; Zhang, Qi; Qin, Jiayin (IEEE transactions on communications, 2020)
Incorporating wireless caching in non-orthogonal multiple access (NOMA) networks is a promising technique to reduce the delivery latency and improve the quality of service. In this paper, we study a cache content placement optimization problem in a cellular NOMA downlink wireless caching network. Our goal is to minimize the average transmit power under the cache capacity constraints. The optimization problem is a non-linear integer programming, which is non-deterministic polynomial-time hard. To efficiently solve the problem, an alternating upper plane method based on quadratic knapsack problem (QKP) is proposed. To deal with the general situation that the sizes of files and cache capacities are not integers, an alternating method based on semidefinite relaxation is also proposed. Finally, a constrained concave-convex procedure-based iterative method is proposed to further reduce the computational complexity. Simulation results show that our proposed methods are superior to the schemes which cache the most popular files until the cache is full.